Modelagem matemática para otimização de um potencial hidráulico utilizando turbinas Francis e Kaplan - Pereira, Bruno Santos Alves [UNESP] (2015)
The choice of the turbine's type to be adopted for use on a given hydraulic power plant is made, as from the application of tables deployed by the manufacturers of the equipment, on function, basically, of the flow and the high of the water drop available at hydraulic potential location. For some specific ranges of these values it is acceptable the use of both Francis turbine and Kaplan turbine. Analysing these two types of turbines, for the choice of the type be based on economic and technical criteria, it is noted that Francis turbine has a lower investiment cost comparing with Kaplan turbine but has an operational limit (in function of the variation of available flow) lower than that one acceptable by Kaplan turbine. Thus, the proposal of this work consists of the analysis of the investiment value for the application of each type of turbine versus the quantity of generated power along the year (considering the operational limits of each type of turbine) for a hydraulic potential that presents a substantial flow variation during the year. For this goal was developed a computer tool whose purpose is determine (considering a hydraulic potential which are known the quantity of generating units, the reference head, the reference flow and the incoming flows serie) which one generating unit should be Francis and which one should be Kaplan in order to obtain the higher profit generated by the sale of the eletricity after one whole of hydropower plant operation. The optmization model was validated from values of UHE Sinop with data available on government agencies and has results compatible with what was effectively implemented